PHYSICAL CHARACTERIZATION OF ALUMINA (Al2O3) BASED REFRACTORY APPLIED ON INDUCTION FURNACE LINING - Ronald Sabtendra; Sri Nugroho; Yusuf Umardani (JURNAL TEKNIK MESIN, 2013)
The broad variety of pyro-processing applications across industry demands great diversity in the supply of refractory materials. In fact, many of these materials have been developed specifically to meet the service conditions of a particular process. The characteristic properties of each refractory class are a function of both their raw materials base and the methods used to manufacture the refractory products. This study aims to characterize alumina (Al2O3) based refractory materials applied on induction furnace lining based on its physical properties such as: the shape and grain size; chemical composition; and density of the specimens which sintered at various temperature. From the X-ray Diffraction Test compared with specification data from the manufacturer, the main composition of the base refractory material used in this study is alumina (Al2O3) with a low amount (less than 10%) of magnesia (MgO) and silica (SiO2). Alumina refractory material consists of coarse grains (with its size larger than 0,85mm) and fine grains (size is equal to 0,15mm or smaller). Grains shape of the  aggregates are mostly angular with its sharp edges. Values of density at temperature 1100C, 10000C, 13000C, 15000C in sequence are 2,92 g/cm3; 2,66 g/cm3;  2,80 g/cm3; 2,98 g/cm3. Density of the refractory will increase as the increase of sintering temperature.